2012
DOI: 10.5402/2012/572421
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Network in Simulation of Supercritical Extraction of Valerenic Acid from Valeriana officinalis L.

Abstract: Application of artificial neural network (ANN) has been studied for simulation of the extraction process by supercritical CO 2 . Supercritical extraction of valerenic acid from Valeriana officianalis L. has been studied and simulated according to the significant operational parameters such as pressure, temperature, and dynamic extraction time. ANN, using multilayer perceptron (MLP) model, is employed to predict the amount of extracted VA versus the studied variables. Three tests, validation, and training data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Currently, the MLP network has widely used among the researcher in any areas of studies such as in grading the essential oil, pattern recognition, oil industry and many others [16]- [23]. MLP successfully implement in estimating the extraction yield on Oregano and Valerian essential oil [16], [17]. Researcher [17] used training algorithms; SCG, RBP, LM and Gradient Descent, while researcher [16] only used LM algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the MLP network has widely used among the researcher in any areas of studies such as in grading the essential oil, pattern recognition, oil industry and many others [16]- [23]. MLP successfully implement in estimating the extraction yield on Oregano and Valerian essential oil [16], [17]. Researcher [17] used training algorithms; SCG, RBP, LM and Gradient Descent, while researcher [16] only used LM algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…MLP successfully implement in estimating the extraction yield on Oregano and Valerian essential oil [16], [17]. Researcher [17] used training algorithms; SCG, RBP, LM and Gradient Descent, while researcher [16] only used LM algorithm. The only similarities in both research studies are the results obtained showed that LM algorithm performed good accuracy with minimum error.…”
Section: Introductionmentioning
confidence: 99%